2010
DOI: 10.3390/ma3063518
|View full text |Cite
|
Sign up to set email alerts
|

Silicone Resin Applications for Ceramic Precursors and Composites

Abstract: This article reviews the applications of silicone resins as ceramic precursors. The historical background of silicone synthesis chemistry is introduced to explain the production costs and supply availability of various silicones. Thermal degradation processes of silicones are classified in terms of the main chain structure and cyclic oligomer expulsion process, which determine the resulting ceramic yield and the chemical composition. The high temperature decomposition of Si-O-C beyond 1,400 °C in an inert atmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(54 citation statements)
references
References 48 publications
3
51
0
Order By: Relevance
“…Because silicone resins can accept various kinds of fillers, plasticizers, blowing agents and cross-linking agents, a proper control over cell size, cell density and cell connectivity is fundamentally possible by employing simple plastic-foaming methods [34]. Excellent dimensional stability after the pyrolysis of the polysiloxane-derived porous ceramics is associated with the thermosetting nature and high ceramic yield of silicones.…”
Section: Cross-linking Of Polysiloxanesmentioning
confidence: 99%
See 3 more Smart Citations
“…Because silicone resins can accept various kinds of fillers, plasticizers, blowing agents and cross-linking agents, a proper control over cell size, cell density and cell connectivity is fundamentally possible by employing simple plastic-foaming methods [34]. Excellent dimensional stability after the pyrolysis of the polysiloxane-derived porous ceramics is associated with the thermosetting nature and high ceramic yield of silicones.…”
Section: Cross-linking Of Polysiloxanesmentioning
confidence: 99%
“…The cross-linked elastomers can accept relatively high extension without cracks when compared to other polycarbosilane, polysilazane and polysilanes. This particular property is useful to shape the starting materials into desired forms by molding, casting, injection, impregnation or extrusion [34]. The advantages of using polysiloxane precursor for porous ceramics include easy storage and processing, the highest ceramic yield [37], low processing temperature (1000-1200…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The peaks at 36, 40, 50, and 54°s uggest the existence of aluminum silicate. Some papers have reported that siloxanes can easily form glass or nanocrystalline aluminum silicate after heating, 14)16) so the presence of aluminum silicate was reasonable. In addition, there were many tiny peaks in the pattern, which may indicate the presence of polycrystalline aluminum silicate phases.…”
Section: Resultsmentioning
confidence: 99%